Feminist Sociology Confluences With Sport Science: Insights, Contradictions, and Silences in Interviewing Elite Women Athletes About Low Energy Availability. (June 2022) - Schofield, Katherine L.; Thorpe, Holly; Sims, Stacy T.
This article explores the socio-cultural dimensions of elite sportswomen's experiences of low energy availability (LEA), focusing particularly on elite track cyclists. With a multidisciplinary research team (two sport scientists and a feminist sociologist), the project began with a suite of quantitative measures that identified five of eight women track cycling athletes categorized with LEA and three athletes categorized with sub-optimal energy availability. This was then followed by semi-structured interviews that revealed the athletes' complex relationships with body image, menstruation, and nutrition practices, and varied experiences of LEA. Bringing the qualitative data into dialogue with the previously collated physiological data, however, helped us acknowledge the silences and deflection strategies among those with more severe cases of LEA. Ultimately, this article offers original insights both into elite track cyclists' understandings of body image, menstruation, and nutrition as associated with LEA, and important reflections on the challenges of doing interviews with sportswomen on sensitive topics in high-performance sporting environments.